Analisis Perbedaan Kecenderungan Keputusan Investasi Melalui Literasi Keuangan dan Profil Investasi - Muhammad Armand Irsyad Rabbani Lubis Lubis; Eka Sudarmaji; Aulia Keiko Hubbansyah (Jurnal Ilmiah Akuntansi Pancasila (JIAP), 2022)
This study aimed to determine the Analysis of Differences in Investment Decision Tendencies through Literacy Through Financial Literacy and Investment Profiles. The data used are primary data with non-probability sampling technique using purposive sampling method for 2018 and 2019 Faculty of Economics and Business students at Pancasila University who want, are, or have not invested in the capital market. Respondents in the study amounted to 125 respondents. The analytical technique used was the discriminant analysis and logistic regression using a software tool, namely SPSS (Statistical Package for the Social Sciences). This study proved that the financial literacy variable could increase the probability of investment decision tendencies. Investment profile variables could increase the probability of investment decision tendencies.